Simulation of In Bag Fertilizer Loading Process In Port of Petrokimia Gresik to Increase Loading Rate - Wahyudi Putra, Bagusranu; Pujawan, I Nyoman (Institut Teknologi Sepuluh Nopember, 2020)
Pelabuhan Petrokimia Gresik is one of the element to support the goverment regarding to maintain stability of fertilizer loading speed. The issue that occurs at Pelabuhan Petrokimia Gresik is the low speed of loading of fertilizer in the bag for the past 4 years. The low speed of loading fertilizer in bag tends to affect its cost. This study aims to simulate the process of loading fertilizer in bag at the Port of Petrokimia Gresik in order to find out the factors which influence the speed deterioration of fertilizer bagging process and applicable alternative scenarios to improve the process of loading fertilizer in bag. Simulations were executed using discrete simulation methods. The results show that loading speed downturn are influenced by significant factors as follows: high loading preparation time at the dock, which consumes 29,35% of loading activity; the high loading time at the dock, which reaches 23,15% of loading activity; also the extensive duration of truck commute from the warehouse to the pier which utilizes 22,95% of loading activity. This study evaluate 7 alternative improvement scenarios. According to ROI perspective, it is preeminent to additionally put field internal control personnel at each shift when loading fertilizer in bag, which can increase the loading speed to 668,29 tons / day, of investment (ROI) of 68% will be obtained within 1 year and the payback period will approximately result in 0,60 years. The best scenario in terms of loading speed is to add internal control personnel and apply a new method of loading fertilizer using a sling bag with an increase in loading rate to 804.17 tons / day, following ROI value of 23% within one year and a PP value of 0.81 year.